Blood Transfusion Incidence and Sociodemographics Relationship with Anxiety Levels of Thalassemia Major Parents - Safyudin; Dita Tri Ramadianti; Subandrate; Liniyanti D. Oswari; Eka Handayani Oktharina (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. Thalassemia is inherited anemia in an autosomal recessive manner with a disruption in hemoglobin synthesis that causes a decreased amount of hemoglobin and anemia. Routine blood transfusions carried out by sufferers and parents' sociodemographic factors can cause an increased psychological burden on the patient's parents. This study investigated the relationship between the incidence of blood transfusions in pediatric patients and parents' sociodemographics with the anxiety level of parents in pediatric thalassemia major patients at RSMH Palembang. This study used an observational analytical method with a cross-sectional study design. Methods. This study used an observational analytical method with a cross-sectional study design. This study consisted of 42 respondents. This study used primary data from interviews and filling out the Z-SAS questionnaire and secondary data from medical records. Results. The distribution of blood transfusion found in thalassemia major children who had transfusions £1 time/month was 40.5%. Based on sociodemographics, 81% of respondents were women, 26.2% had a low level of education, 28.6% were in early adulthood, 61.9% had less income, 81% had 1 child, and 14.3% had thalassemia Major children diagnosed £1 year. The level of anxiety that dominated the results was normal/not anxious (72.8%) and mild anxiety (26.2%). (P Value= 0.305; 0.174; 1.00; 0.095; 0.158; 0.657; 0.644). Conclusion. There was no relation between blood transfusion incidence in children with thalassemia major and sociodemographic of parents with anxiety levels of children with thalassemia major parents in RSMH Palembang.